A recent collection of Polyporus udus from type locality (Indonesia) - Ivan Permana Putra; Oktan Dwi Nurhayat; Mada Triandala Sibero; Sitti Aida Adha Taridala; Rudy Hermawan; Zulhan Arif (Acta Scientiarum. Biological Sciences, 2025)
Polyporus udus (Bresadolia uda) was initially described as originating from Indonesia. Few recent studies showed that P. udus was placed in doubtful taxonomical treatment in Polyporus. There is no recent collection of this genus accessible from type locality after approximately two centuries. Therefore, this study aimed to update the current data and show the taxonomic position of P. udus to previous reports globally. During the wild mushroom survey 2023, the stipitate basidiomata of Polyporus was obtained. The morphology of the basidiomata was described based on the macroscopic and microscopic features. The molecular analysis and phylogenetic tree construction were performed using the ITS 1/2 sequence. The results showed that the combination of morphological and molecular analyses confirmed the taxonomical position of the specimens as B. uda (Jungh.). Bresadolia uda BO24625 grew in solitary to caespitose, basidia clavate, basidiospores cylindrical to sub-ellipsoid. Based on the phylogenetic tree, our specimens were in the same clade as those from Lao and China but different compared to the United States of America (USA) and India. In conclusion, this study provided the first morphological dimension of basidiospores and molecular information on P. udus from type locality and could be used for future investigation of Polyporus.